KOMUNIKASI ANTARAGAMA DAN TOLERANSI DI DESA BALONG GARUT, SIDOARJO - Khairunnisa, Chessa Adya; Nur Majidah, Yusnita Cindi (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2024)
This study aims to analyze the role of interreligious communication in maintaining tolerance in Balong Garut Village, Krembung District, Sidoarjo Regency. The village consists of a community with two major religions, Hinduism and Islam. The issue addressed is how interreligious communication can foster tolerance and harmony, as well as the barriers that may arise due to differences in culture, traditions, and religious beliefs. This research employs a descriptive qualitative method with data collection techniques through in-depth interviews and participatory observations with village residents. The findings reveal that open and cooperative interpersonal communication plays a crucial role in strengthening tolerance between religious communities, both in daily life and during shared social activities. Communication barriers, such as differences in traditions, culture, and beliefs, can be overcome through more intensive dialogue, cross-cultural education, and close cooperation between religious groups. This research contributes to the field of communication studies by highlighting the importance of intercultural communication in creating harmony in multicultural societies, especially in religious communities.